The never game [compact disc, unabridged] - Deaver, Jeffery (Deaver, Jeffery. Colter Shaw series, 2019)
Hired to locate a missing young woman from Silicon Valley, Colter Shaw finds himself tracking a madman who stages scenes from his favorite game.